A molecular phylogeny of Afromontane dwarf geckos (Lygodactylus) reveals a single radiation and increased species diversity in a South African montane center of endemism - Travers, Scott L.; Jackman, Todd R.; Bauer, Aaron M. (Molecular phylogenetics and evolution, 2014)
[Display omitted] •A multilocus phylogeny of montane Lygodactylus in southeast Africa is presented.•We test biogeographic and taxonomic hypotheses for two Afromontane species groups.•We reveal geographically circumscribed patterns of Afromontane diversification.•Current species groups and several polytypic taxa are not monophyletic.•We elevate several subspecies and present a new group-level classification. Afromontane habitats throughout eastern sub-Saharan Africa support remarkable levels of microendemism. However, despite being the subject of decades of research interest, biogeographical patterns of diversification throughout this disjunct montane system still remain largely unknown. We examined the evolutionary relationships of diurnal dwarf geckos (Lygodactylus) from several Afromontane regions throughout southeastern Africa, focusing primarily on two species groups (rex and bonsi groups). Using both mitochondrial and nuclear markers, we generate a molecular phylogeny containing all members of the rex and bonsi groups, to evaluate the monophyly of these groups along with previous biogeographic hypotheses suggesting independent southward invasions into the greater Drakensberg Afromontane center of endemism in northeastern South Africa by each group. Our results provide no support for these taxonomic and biogeographic hypotheses, and instead reveal geographically circumscribed patterns of diversification. One clade is restricted to the highlands of southern Malawi and northern Mozambique and the other to the greater Drakensberg region of northeastern South Africa and Swaziland. Interestingly, L. bernardi from the Nyanga Highlands of eastern Zimbabwe is nested within the primarily savanna-dwelling capensis group. We use Bayesian species delimitation methods to evaluate species limits within the greater Drakensberg clade, which support the elevation of the subspecies of L. ocellatus and L. nigropunctatus, thus bringing the total to eight species within a relatively confined geographic area. These results further highlight the greater Drakensberg Afromontane region as both an important center of endemism, as well as a center of diversification contributing to the accumulation of southern Africa’s rich species diversity.